Minimal Impairment in a Rat Model of Duration Discrimination Following Excitotoxic Lesions of Primary Auditory and Prefrontal Cortices - Pai, Shraddha S.; Erlich, Jeffrey C.; Kopec, Charles; Brody, Carlos D. (Frontiers in Systems Neuroscience, 2011)
We present a behavioral paradigm for the study of duration perception in the rat, and report the result of neurotoxic lesions that have the goal of identifying sites that mediate duration perception. Using a two-alternative forced-choice paradigm, rats were either trained to discriminate durations of pure tones (range=[200,500]ms; boundary=316ms; Weber fraction after training=0.24+/-0.04), or were trained to discriminate frequencies of pure tones (range=[8,16]kHz; boundary=11.3kHz; Weber=0.16+/-0.11); the latter task is a control for non-timing-specific aspects of the former. Both groups discriminate the same class of sensory stimuli, use the same motions to indicate decisions, have identical trial structures, and are trained to psychophysical threshold; the tasks are thus matched in a number of sensorimotor and cognitive demands. We made neurotoxic lesions of candidate timing-perception areas in the cerebral cortex of both groups. Following extensive bilateral lesions of the auditory cortex, the performance of the frequency-discrimination group was significantly more impaired than that of the duration-discrimination group. We also found that extensive bilateral lesions of the medial prefrontal cortex resulted in little to no impairment of both groups. The behavioral framework presented here provides an audition-based approach to study the neural mechanisms of time estimation and memory for durations.